O ethos musical grego e o critério musical pitagórico na origem da liturgia musical cristã: um estudo sobre valências afetivas na música litúrgica medieval - Valdetaro, Alexandre Barbosa (2024)
This study in religion studies, investigates the convergence between the Greek ethos and early Christian liturgical music, focusing on the influence of Pythagorean musical rationality on the formation of the liturgy and the spirituality of the faithful. The research analyzes the adoption of Greek modes by the Early Church, highlighting the importance of Gregory I in standardizing sacred music as a means of non-verbal emotional communication. In addition to addressing the historical impact of this unification, the study explores how music, through the Greek modes, regulated emotions and promoted social cohesion, consolidating a new musical ethos for Christianity. The work also discusses the modern psychological implications of the relationship between music and emotion, using neuroscientific and empirical studies that validate the influence of music on the religious and spiritual experience of the faithful, reaffirming the central role of music in shaping a Christian collective identity and its relevance in contemporary liturgical practices